Assessments of k-kL Turbulence Model Based on Menter’s Modification to Rotta’s Two-Equation Model - Khaled S. Abdol-Hamid (International Journal of Aerospace Engineering)
The main objective of this paper is to construct a turbulence model with a more reliable second equation simulating length scale. In the present paper, we assess the length scale equation based on Menter’s modification to Rotta’s two-equation model. Rotta shows that a reliable second equation can be formed in an exact transport equation from the turbulent length scale and kinetic energy. Rotta’s equation is well suited for a term-by-term modeling and shows some interesting features compared to other approaches. The most important difference is that the formulation leads to a natural inclusion of higher order velocity derivatives into the source terms of the scale equation, which has the potential to enhance the capability of Reynolds-averaged Navier-Stokes to simulate unsteady flows. The model is implemented in the CFD solver with complete formulation, usage methodology, and validation examples to demonstrate its capabilities. The detailed studies include grid convergence. Near-wall and shear flows cases are documented and compared with experimental and large eddy simulation data. The results from this formulation are as good or better than the well-known shear stress turbulence model and much better than k-ε results. Overall, the study provides useful insights into the model capability in predicting attached and separated flows.